Vom mehrstimmigen Choral-Satz und Liedmotette zum Generalbaßlied : das Repertoire der handschriftlichen lutherischen Chorbücher des 17. Jahrhunderts aus Oberungarn - Peter Ruščin (Musicologica Brunensia, 2020)
The lutheran manuscript Choral Books from the 17th century preserved in the territory of Slovakia contain a lot of simple polyphonic Chants and Hymns, especially with German, but also Latin, Hungarian and Czech texts. Almost all of preserved manuscripts comes from Upper Hungary (contemporary Eastern Slovakia). The repertory of the manuscript sources includes arround 300 polyphonic compositions, mostly German origin. There are ca. 50 compositions from (mostly anonymous) local composers in this sources, from small polyphonic works in the traditional style of choral motet or metrical hymn with cantus firmus in discant to spiritual song with figured bass. This various styles of hymn setting stayed in practice in the lutheran churches of Upper Hungary until the early 18th century.